ESTIMASI LIMPAHAN PERMUKAAN DARI DATA SATELIT UNTUK MENDUKUNG PERINGATAN DINI BAHAYA BANJIR DI WILAYAH JABODETABEK - Sofyan, Parwati; Febrianti, Nur; Prasasti, Indah (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2014)
The study about runoff estimation based on soil moisture conditions was conducted using remote sensing data i.e., Landsat and Tropical Rainfall Measurement Mission during flood period January – February 2013 in Jakarta and its souroundings area. The Landsat data used to analyze the landcover/landuse which one of the basin characteristics. In this study, the TRMM has ability for representing the regional rainfall as 62.5 %. The Curve Number-Soil Conservation Service (CN-SCS) method was used in this study to estimate the runoff. The results of runoff estimation was shown in hydrograph unit in order to know when the flood will occur. The antecedent soil moisture condition in wet condition showed the best hydrograph unit. It had the peak point in January 17th 2013 exactly same with the time flood occurred in Jakarta and the souroundings area. This model has a good potential to be used as a flood early warning system. Spatially, the overall accuracy of the flood identification in Jakarta region compared with the flood map produced by Disaster Management Berau was 43 % with the producer’s accuracy 96 %, and user’s accuracy 42 %.